2020
DOI: 10.3390/molecules25245814
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Complexes with Nitrogen Donor Ligands as Anticancer Agents

Abstract: The search for anticancer metal-based drugs alternative to platinum derivatives could not exclude zinc derivatives due to the importance of this metal for the correct functioning of the human body. Zinc, the second most abundant trace element in the human body, is one of the most important micro-elements essential for human physiology. Its ubiquity in thousands of proteins and enzymes is related to its chemical features, in particular its lack of redox activity and its ability to support different coordination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(64 citation statements)
references
References 228 publications
(115 reference statements)
0
63
0
1
Order By: Relevance
“…3) 23 . The Zn-based coordination bonds could form between the carboxylate groups grafted on EPDM backbones and the polar functional groups in lignin such as the phenoxy and carboxylate groups 24 , which was confirmed by FTIR spectra in Fig. 2a.…”
Section: Resultsmentioning
confidence: 58%
“…3) 23 . The Zn-based coordination bonds could form between the carboxylate groups grafted on EPDM backbones and the polar functional groups in lignin such as the phenoxy and carboxylate groups 24 , which was confirmed by FTIR spectra in Fig. 2a.…”
Section: Resultsmentioning
confidence: 58%
“…Metal complexes like Zn(II) may enter the cancer cell, permeate the nucleus, mitochondria, cytoplasm, and exert their anti-tumor effect. Previous studies mostly focused on DNA interactions, although TOPO-I-II, p53, nuclease were reported to be the alternative targets [15]. We are of the opinion that there is a need for detailed studies to determine the potential targets of Zn(II) complexes.…”
Section: Chemotherapy and Electrochemotherapymentioning
confidence: 99%
“…Besides these functions, it has some bene cial therapeutic/preventive effects on cancer. Recent research has revealed that Zn(II) derivatives could be potentially used as an anticancer agent with low adverse effects and toxicity and different modes of action and cellular targets compared to the traditional metal-based drugs [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, nitrogen-donor chelating ligands have been widely used in the architectural design of metal complexes with biological applications, including cytotoxic activities. [4][5][6][7] For instance, Singh et al synthesized a series of 5-iodouracil complexes with Mn(II), Co(II), Cu(II), Zn(II) and Cd(II) ions, some of which were active against Sarcoma-180 and L929 tumor cells. 8 Later, the effects of 5-bromouracil complexes with Cr(III), Fe(III) and Al(III) were reported on P815 murine mastocytoma.…”
Section: Introductionmentioning
confidence: 99%